Preferensi Mahasiswa Dalam Memilih Perguruan Tinggi Swasta Di Kota Malang - Nurwahdania Nurwahdania; Pardiman Pardiman; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2022)
Absttract This study aims to determine student preferences in choosing private universities in the city of Malang. The sample in this study amounted to 96 people who are students from the University of Muhammadiyah Malang, the Islamic University of Malang and the University of Merdeka Malang. The sampling technique used is purpusive sampling. The data used in the study used primary data and secondary data. The method used is conjoint analysis with the help of the SPSS version 25 program. The results of the research on student preferences in choosing private universities in the city of Malang can be seen that the most important attribute is accreditation with an importance level of 24.440%. The value of this attribute is greater than the value of other attributes such as college facilities by 23.302%, education costs by 17.925%, promotions by 17.277% and location of universities by 17.056%. Keywords : Preferences, Facilities, Cost, Accreditation Location, Promotion.